2014
DOI: 10.1038/srep03840
|View full text |Cite
|
Sign up to set email alerts
|

Atractylenolide-I Sensitizes Human Ovarian Cancer Cells to Paclitaxel by Blocking Activation of TLR4/MyD88-dependent Pathway

Abstract: Paclitaxel, a known TLR4 ligand, leads to activation of TLR4/MyD88-dependent pathway that mediates chemoresistance and tumor progression in epithelial ovarian carcinoma (EOC). Atractylenolide-I (AO-I), a novel TLR4-antagonizing agent, inhibits TLR4 signaling by interfering with the binding of LPS or paclitaxel to membrane TLR4 of human leukocytes. In this study, AO-I was found to attenuate paclitaxel-induced protein expression of IL-6, VEGF and survivin, and to enhance early apoptosis and growth inhibition in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
42
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(46 citation statements)
references
References 39 publications
3
42
1
Order By: Relevance
“…In the present study, we provided evidence demonstrating the anti-lung cancer effects of ATL-l. The doses of ATL-1 in the current study were similar or even lower than those reported by others demonstrating substantial anti-cancer responses in several cancer types [13, 45, 49]. Our results showed that ATL-1 inhibited lung cancer cell growth through ERK1/2-mediated suppression of Stat3 and SP1 protein expressions.…”
Section: Discussionmentioning
confidence: 41%
“…In the present study, we provided evidence demonstrating the anti-lung cancer effects of ATL-l. The doses of ATL-1 in the current study were similar or even lower than those reported by others demonstrating substantial anti-cancer responses in several cancer types [13, 45, 49]. Our results showed that ATL-1 inhibited lung cancer cell growth through ERK1/2-mediated suppression of Stat3 and SP1 protein expressions.…”
Section: Discussionmentioning
confidence: 41%
“…TLR4 also has been identified at the protein level in breast epithelial tumor cells (5). In contrast to its role in tumor-associated immune cells, TLR4 promotes growth (6) and chemotherapeutic resistance (7,8) in ER-negative breast cancer cell lines, in accordance with studies of ovarian cancer (9,10). Based on these studies, therapies targeting TLR4 appear to be novel viable strategies with significant potential for treating cancer, and have in fact been proposed as such (6)(7)(8).…”
mentioning
confidence: 72%
“…and exerts a wide range of pharmacological activities, including anti-inflammatory (11,12), anti-tumor (13,14) and anti-angiogenic effects (15). A previous study has implied a potential anti-depressive activity of AT-I (16).…”
Section: Introductionmentioning
confidence: 99%